Resveratrol regulates muscle fiber type gene expression through AMPK signaling pathway and miR-22-3p in porcine myotubes. Issue 3 (1st June 2022) - Wen, Wanxue; Chen, Xiaoling; Huang, Zhiqing; Chen, Daiwen; Yu, Bing; He, Jun; Yan, Hui; Luo, Yuheng; Chen, Hong; Zheng, Ping; Yu, Jie
Abstract: This study aimed to investigate the effect and underlying mechanisms of resveratrol on porcine muscle fiber type gene expression in porcine myotubes. Here, results showed that resveratrol treatment significantly promoted slow myosin heavy chain (MyHC) and inhibited fast MyHC in porcine myotubes. The phosphorylation of adenosine monophosphate-activated protein kinase (AMPK) and the downstream factors of AMPK signaling, such as Sirtuin1 (Sirt1) and peroxlsome proliferator-activated receptor-γ coactlvator-1α (PGC-1α), were also increased by resveratrol, suggesting that resveratrol could activate the AMPK signaling pathway. Interestingly, resveratrol inhibited the expression of miR-22-3p in porcine myotubes. Furthermore, AMPK inhibitor compound C and miR-22-3p mimic effectively eliminated the effects of resveratrol on slow MyHC and fast MyHC expressions in porcine myotubes. Taken together, our findings indicate that resveratrol regulates muscle fiber type gene expression through the AMPK signaling pathway and miR-22-3p in porcine myotubes.